2009
DOI: 10.1038/mp.2009.110
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells increase hippocampal neurogenesis and counteract depressive-like behavior

Abstract: Adult bone marrow-derived mesenchymal stem cells (MSCs) are regarded as potential candidates for treatment of neurodegenerative disorders, because of their ability to promote neurogenesis. MSCs promote neurogenesis by differentiating into neural lineages as well as by expressing neurotrophic factors that enhance the survival and differentiation of neural progenitor cells. Depression has been associated with impaired neurogenesis in the hippocampus and dentate gyrus. Therefore, the aim of this study was to anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(72 citation statements)
references
References 79 publications
5
66
1
Order By: Relevance
“…For example, it was determined that deep brain stimulation had an AD-like effect in the FSL rat (Friedman et al, 2012). Earlier, they have shown that stem cell injections also had an AD-like effect (Tfilin et al, 2010). Through collaborators in England, Yadid has examined elevations in arachidonic acid in the FSL rats (Green et al, 2009).…”
Section: Recent and Current Researchmentioning
confidence: 99%
“…For example, it was determined that deep brain stimulation had an AD-like effect in the FSL rat (Friedman et al, 2012). Earlier, they have shown that stem cell injections also had an AD-like effect (Tfilin et al, 2010). Through collaborators in England, Yadid has examined elevations in arachidonic acid in the FSL rats (Green et al, 2009).…”
Section: Recent and Current Researchmentioning
confidence: 99%
“…Quantitative PCR analysis was performed with Mastercycler Realplex (Eppendorf, Hamburg, Germany) using SYBR Green Realtime PCR Master Mix (Toyobo, Osaka, Japan). The primers were: Tuj1 forward, tagaccccagcggcaactat; Tuj1 reverse, gttccaggttccaagtccacc (PrimerBank); Dcx forward, ggggattgtgtacgctgttt; Dcx reverse, cgaccagttgggattgacat; Map-2 forward, caaacgtcattactttacaacttg; Map-2 reverse, cagctgcctctgtgagtgag; Gfap forward, ggtggagagggacaatctc; Gfap reverse, ccagctgctcctggagttct [26]; b-actin forward, gtcttcccctccatcgtggg; b-actin reverse, tggctggggtgttga aggtc.…”
Section: Rna Isolation and Quantitative Rt-pcr (Rt-qpcr) Analysismentioning
confidence: 99%
“…Indeed, MSCs have been used for treatment of bone disorders such as in children with osteogenesis imperfecta, in whom allogeneic MSCs were engrafted and shown to enhance growth [2], repair of large defects in long bones when incorporated with biomaterial scaffolds [3], treatment of an atrophic tibial diaphyseal nonunion [4], reconstruction of a major maxillary defect, and reconstruction of jaw defects prior to dental implant placement [5,6]. Other promising clinical applications for MSCs come from their indirect immune-regulatory and paracrine action in a variety of clinical situations, such as reducing graftversus-host disease after hemopoietic stem cell (HSC) transplantation [7]; improving engraftment of HSCs [8]; and enhancing cardiac [9,10], liver [11], and neural repairs [12]. MSCs have been also used as vehicles for delivery of therapeutic gene products and agents to tumor and cancer sites [13].…”
Section: Introductionmentioning
confidence: 99%